History as a 'GPS': On the uses of historical narrative for French Canadian students' life orientation and identity (UCL Press, 2017)
This article presents the results of a study that analyses students' historical narratives of the nation in relation to historical consciousness and how their sense of self-identification with groups affects their narrative structure and orientation. This study was conducted with French Canadian students registered in two high schools (n=58) and one university (n=18) in Ottawa, the federal capital of Canada. I found that a strong sense of identification leads young people to construct more engaging and militant stories of the collective past, with greater historical appropriation (using the collective 'we') and a sense of continuity with past actualities. I then discuss the implications of this study for research on the narrative competence of historical consciousness and what history education might do in school to promote historical consciousness in Canada.